Trudności w uczeniu się – model diagnozowania dysleksji rozwojowej - Szkolak-Stępień, Anna (Studia Edukacyjne, 2018)
The article by Anna Szkolak-Stępień concerns specificdifficultiesin learning reading and writing. The choice of the topic results from the changes in the Polish educational reality at the time of social, political and cultural transformation. The article presents the complexity of the educational environment of the modern child and the functioning of Polish schools in the reform period. Modern times impose on the teacher increasingly complex tasks, requiring new professional competences, which will include new types of teaching methods, methodological considerations and a new quality of professional performance.